Dynamic interaction effects of buried structures on seismic response of surface structures - Sisman, Rafet; Ayvaz, Yusuf (TECHNO-PRESS, 2020)
This study presents an investigation of the dynamic interactions between a surface structure lying on two different soil deposits and a square-shaped buried structure embedded in the soil. To this end, a large number of numerical models are generated by using a well-known Finite Element Method software, i.e., OpenSEES. The interaction phenomenon is assumed to be affected by six different parameters. In the parametric study, these parameters are assumed to have various values in accordance with the engineering practices. A total of 1620 possible combinations of the parameter values are addressed in this study. 30 different numerical models are also generated as the 'free-field cases' to set a reference. The surface structure drift and acceleration amplifications are used as a measure to evaluate the dynamic interactions. The response (i.e., drifts and accelerations) amplifications are calculated as the ratio of the maximum surface structure response in any 'case' to the maximum surface structure response in corresponding free-field case. Variation of the response amplifications with any of the investigated parameters is addressed in this paper. The results obtained from the numerical analyses clearly reveal that the presence of a buried structure in the vicinity of a surface structure can cause both amplification and de-amplification of the surface structure responses, depending on the case parameters.
Keywords: soil structure interaction; soft soil site; buried structure; surface structure; UNDERGROUND CAVITIES; GROUND RESPONSE; TUNNELS; AMPLIFICATION; EARTHQUAKE; ADJACENT; Engineering